Proteomic Analysis of the Fusarium graminearum Secretory Proteins in Wheat Apoplast Reveals a Cell-Death-Inducing M43 Peptidase - Pengfeng Li; Ruihua Zhao; Ying Fang; Yujin Fan; Qianyong Hu; Wei Huang; Wujun Ma; Cuijun Zhang (Journal of Fungi)
Fusarium graminearum, a highly destructive fungal pathogen, poses a major threat to wheat production. The apoplast is an important space for plant–pathogen interactions. However, no studies have been reported on the secretory proteins of F. graminearum in the wheat apoplast. In this study, we performed mass spectrometry analysis of F. graminearum secretory proteins in wheat apoplast and identified 79 potential secretory proteins. We identified a metalloprotease (referred to as Fg28) and demonstrated its capacity to induce cell death and reactive oxygen species (ROS) accumulation in Nicotiana benthamiana. Fg28 is strongly up-regulated in the early stages of infection and is secreted into the intercellular space of wheat cells. Full-length Fg28 is required to induce cell death in N. benthamiana. In addition, Fg28 induces an immune response that is independent of BAK1/SOBIR1 and EDS1/PAD4. Furthermore, knocking out Fg28 had no effect on morphology or pathogenicity. In conclusion, we have identified a set of F. graminearum secreted proteins in the wheat apoplast and a metalloproteinase that triggers immune response, providing new insights into understanding the interaction between F. graminearum and wheat.